2022
DOI: 10.1186/s12888-022-04393-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of depression, anxiety, and stress among high school students in, Northwest Ethiopia, 2021

Abstract: Background Many studies have revealed that students’ performance in school, is affected by symptoms of depression, anxiety, and stress, which may impair their academic achievement, and lead to school dropout. However, to date, no studies have evaluated these three disorders among high school students in Africa. Therefore, in this study, we aimed to assess the prevalence of depression, anxiety, stress, and their associated factors among high school students in Northwest Ethiopia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 43 publications
4
18
2
2
Order By: Relevance
“…Association of sociodemographic factors with anxiety symptoms in the present study was consistent with most previous studies. Older age,32 living in rural areas,41 coming from family with low income,40 42 were positively associated with anxiety symptoms, and there was no association between maternal education level and adolescent anxiety symptoms 50. In align with previous studies,40 43 poor academic performance was positively related to anxiety symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…Association of sociodemographic factors with anxiety symptoms in the present study was consistent with most previous studies. Older age,32 living in rural areas,41 coming from family with low income,40 42 were positively associated with anxiety symptoms, and there was no association between maternal education level and adolescent anxiety symptoms 50. In align with previous studies,40 43 poor academic performance was positively related to anxiety symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…Compared to the present study, a lower prevalence of anxiety was reported in studies conducted among school students in Egypt (6.7%) (32), Malaysia (39.7%) (33), and India (17.9%) (34), France (32.7%) (35), South Africa (32.0%) (36), Nigeria (10.3%) (37), China (24.8%) (38), Portugal (6.5%) (39), UAE (28.0%) (40), Sri Lanka (28.0%) (41), Bangladesh (18.1%) (42), Saudi Arabia (34.2%-65.0%) (43), and Turkey (42.0%) (44). A higher prevalence of anxiety has been reported in studies among university students conducted in Iran (85.0%) (45), Lebanon (73.2%) (46), and Northwest Ethiopia (66.7%) (47). A systematic review and meta-analysis reported that globally, 34.8% of graduate students suffer from anxiety (95% CI: 29.5-40.5%).…”
Section: Discussionmentioning
confidence: 98%
“…En lo que respecta a las variables sociodemográficas asociadas a la prevalencia de los TMC, se determinó que las principales eran el género femenino (2,5,7-10), el nivel de consumo de bebidas alcohólicas (1,8,9), los antecedentes de familiares con enfermedades mentales (5,11,12) y el apoyo emocional (5,8).…”
Section: Introductionunclassified